EQUATION OF STATE OF GOLD AND ITS APPLICATION TO THE PHASE BOUNDARIES NEAR 660 KM DEPTH IN EARTH'S MANTLE - Shim S.H.; Duffy T.S.; Takemura K. (My University, 2002)
The pressure-volume-temperature equation of state (EOS) of gold is fundamental to high-pressure science because of its widespread use as an internal pressure standard. In particular, the EOS of gold has been used in recent in situ multi-anvil press studies for determination of phase boundaries related to the 660-km seismic discontinuity. These studies show that the boundaries are lower by 2 GPa than expected from the depth of the 660-km discontinuity. Here we report a new P-V-T EOS of gold based on the inversion of quasi-hydrostatic compression and shock wave data using the Mie-Gruneisen relation and the Birch-Murnaghan-Debye equation. The previously poorly constrained pressure derivative of isothermal bulk modulus and the volume dependence of Gruneisen parameter (q=d lnγ/d ln V) are determined by including both phonon and electron effects implicitly: K'0T=5.0+/-0.2 and q=1.0+/-0.1. This combined with other accurately measured parameters enables us to calculate pressure at a given volume and temperature. At 660-km depth conditions, this new EOS yields 1.0+/-0.2 GPa higher pressure than Anderson et al.'s EOS which has been used in the multi-anvil experiments. However, after the correction, there still exists a 1.5-GPa discrepancy between the post-spinel boundary measured by multi-anvil studies and the 660-km discontinuity. Other potential error sources, such as thermocouple emf dependence on pressure or systematic errors in spectroradiometry, should be investigated. Theoretical and experimental studies to better understand electronic and anharmonic effects in gold at high P-T are also needed.
Keywords: EQUATIONS OF STATE; GOLD; 660-KM DISCONTINUITY; MANTLE